Effects of Grape (Vitis Vinifera L.) R2r3-Myb Transcription Factor, MYB6 on Drought Stress Tolerance In Transgenic Tobacco (Bangladesh Journal of Botany, 2025)
The identification of stress-associated genes in grape are essential for improving its drought resistance. In this study, MYB6, a R2R3-MYB in grape ‘Yatomi Rose’ (Vitis vinifera L.) was identified, and the stress response phenotypes of tobacco lines overexpressing this gene were investigated. The results revealed that root lengths, fresh weights, and heights of transgenic tobacco with overexpression of VvMYB6 were significantly different from empty vector-transformed (EV) tobacco under optimum stress conditions. Under drought stress, the leaves of transgenic tobacco with overexpression of VvMYB6 had less blue-brown patches and lighter color compared with the EV-transformed tobacco, which indicates a reduction in the content of reactive oxygen species (ROS). VvMYB6-overexpressing tobacco plants showed less electrolyte leakage, but increased contents of chlorophyll and proline. Additionally, the contents of malondialdehyde (MDA) and H2O2 decreased in VvMYB6-overexpressing tobacco plants owing to increased activity of antioxidant enzymes. This study significantly deepens the understanding of the roles of R2R3-MYB TFs in drought tolerance of plants and facilitates the development of cultivars with enhanced stress tolerance.Bangladesh J. Bot. 54(2): 369-376, 2025 (June)